Horizontal-to-tilt irradiance conversion for high-latitude regions: a review and meta-analysis - Manni, Mattia; Thorning, Jacowb Krum; Jouttijärvi, Sami; Miettunen, Kati; Di Sabatino, Marisa; Lobaccaro, Gabriele (Frontiers in Built Environment, 2023)
This review focuses on the solar irradiance model chain for horizontal-to-tilted irradiance conversion at high latitudes. The main goals of the work are 1) to assess the extent to which the literature accounts for decomposition and transposition models specifically developed for high-latitude application; 2) to evaluate existing validation studies for these particular conditions; 3) to identify research gaps in the optimal solar irradiance model chain for high-latitude application (i.e., latitude ≥60°). In total, 112 publications are reviewed according to their publication year, country, climate, method, and keywords: 78 publications deal with decomposition models and 34 deal with transposition models. Only a few models (6) have been parameterized using data from Nordic countries. Here, we compare 57 decomposition models in terms of their performance in Nordic climate zones and analyze the geographical distribution of the data used to parametrize these models. By comparing the Normalized Root Mean Square Deviation coefficients for direct normal irradiation, the decomposition models Skartveit1 and Mondol1 are most effective on one-hour scale and Yang4 on one-minute scale. Recent studies on the empirical transposition models estimating the global tilted irradiation on vertical surfaces show the best performance for Perez4 and Muneer models. In addition, innovative methods such as artificial neural networks have been identified to further enhance the model chain. This review reveals that a validated model chain for estimating global tilted irradiation at high latitudes is missing from the literature. Moreover, there is a need for a universal validation protocol to ease the comparison of different studies.